Screening of phyllospheric and endophytic bacteria as biocontrol agents of Xanthomonas oryzae pv. oryzae (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Widjayanti T, Kusuma RR, Aini LQ, Fitriani CDA, Sektiono AW, Hadi MS, Setiawan Y. 2023. Screening of phyllospheric and endophytic bacteria as biocontrol agents of Xanthomonas oryzae pv. oryzae. Biodiversitas 24: 2072-2079. The use of phyllospheric and endophytic bacteria as biocontrol agents may be an eco-friendly alternative strategy to control bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo). This study aimed to evaluated the antagonistic potential of phyllospheric and endophytic bacteria against X. oryzae pv. oryzae. The phyllospheric and endophytic bacteria were isolated from organic rice fields in Tumpang Sub-district, Malang District, East Java, Indonesia. The pathogenicity of X. oryzae pv. oryzae was tested on rice plants by the leaf clipping inoculation method. In this study, eight combinations of phyllospheric bacteria (PB) and endophytic bacterial (EB) isolates were chosen based on the highest percentage of inhibition. Streptomycin (positive control) and distilled water (negative control) were also used as a treatment. Identification of selected phyllospheric and endophytic bacteria was carried out through morphological and molecular characteristics. In total, 181 of PB and 76 of EB were isolated from rice plants. Of these, 11 of PB and 13 of EB isolates had potential as antagonists, shown by inhibition zone. Among all treatments, P55+E15 combination showed the highest inhibition zone (83.49%), followed by P55+E27 (82.33%) and P55+E18 (80.98%). Based on morphological and molecular identification, P55, E15, E27, and E18 isolates were identified as Delftia lacustris, Bacillus cereus, Escherichia coli, and Lysinibacillus fusiformis, respectively. The combination of D. lacustris (P55) and B. cereus (E15) can be used as a biocontrol agent against X. oryzae pv. oryzae based on in vitro assay.
Keywords: Bacillus cereus, bacterial consortium, bacterial leaf blight, Delftia lacustris, rice, Xanthomonas oryzae